Dissipated electrical power and electron density in an RF atmospheric pressure helium plasma jet. (24th September 2019) - Golda, J; Kogelheide, F; Awakowicz, P; Gathen, V Schulz-von der
Abstract: Atmospheric pressure plasmas have great potential, especially for biomedical applications, due to the large number of reactive species produced. In particular with regard to these applications, the comparability of processes through appropriate control of plasma parameters is essential for treatment safety. Here we present a method for the operando determination of absolute absorbed power in an RF atmospheric pressure helium plasma discharge using miniaturized probes. A detailed error analysis demonstrates the reliability of the measured power values. With the help of a global model, the sheath width and electron density (4 × 10 16 –11 × 10 16 m −3 ) are derived from these power measurements and compared to literature. The results and thus the validity of the electrical model are confirmed by a second, independent characterization method using optical emission spectroscopy and time-averaged imaging.